2019
DOI: 10.1016/j.micpath.2019.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of small intestinal mucosa from porcine epidemic diarrhea virus infected piglets

Abstract: A B S T R A C TCaused by porcine epidemic diarrhea virus (PEDV), porcine epidemic diarrhea (PED) is an acute infectious disease which causes damage to the intestine including intestinal villus atrophy and shedding, leading to serious economic losses to the pig industry worldwide. In order to obtain detailed information about the pathogenesis and host immune response in a PEDV-infected host for first In vivo study we used high-throughput sequencing to analyze the gene expression differences of the small intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
11
1
Order By: Relevance
“…There is very little information available on the regulation of intestinal transporters in piglets by PEDV infection 2225 . Schweer 26 found that PEDV infection decreased the GLUT2 mRNA level but increased the SLC6A14 level in the piglet jejunum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is very little information available on the regulation of intestinal transporters in piglets by PEDV infection 2225 . Schweer 26 found that PEDV infection decreased the GLUT2 mRNA level but increased the SLC6A14 level in the piglet jejunum.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the omic studies with PEDV-infected pigs, Sun et al . 22 found that PEDV infection enhanced the expression of 7044 genes and most of them were related to the immune response to infectious disease pathways. Of note, based on the KEGG analysis, 374 of the differentially expressed genes (DEGs) are related to nutrient transport and catabolism, and this result is in good agreement with that of our present study.…”
Section: Discussionmentioning
confidence: 99%
“…Most viruses attempt to change host cellular processes and organism systems to improve the efficiency of virus infection, and, on the other hand, the cells employ multiple mechanisms in responses to generating an antiviral state (13,14). As reported, CoV infection can cause alterations in the transcription and translation patterns, cell cycle, cytoskeleton, and apoptosis pathways of host cells (15)(16)(17)(18)(19)(20)(21)(22). With traditional approaches, it is difficult to explore the intricate and mass interactions between viruses and hosts/cells.…”
Section: Introductionmentioning
confidence: 99%
“…Next-generation' sequencing (NGS) technology has provided a powerful tool for the studies of emerging and re-emerging human and animal pathogens/diseases. NGS technology, including whole genome sequencing, RNA-Seq, and single cell sequencing, has been extensively applied in genome sequencing, gene expression profiling analysis, and pathogen detection ( 15 , 23 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…This reliable platform with a high-throughput and powerful tool guarantees the enormous gene study. Across all RNA species, RNA-seq has revolutionized and become a widely used approach to study quantitative aspects of transcriptome profiling in the virus-infected cells Sun et al, 2014Sun et al, , 2019Zhou et al, 2017). In the current study, we have explored the miRNA milieu in CRFK cells infected with CPV-2c Laotian isolates (Puentes et al, 2012).…”
Section: Discussionmentioning
confidence: 99%